The Join and Distinction-Union: A Resonant and Complex Oneness - Adam Shechter (EJP import test, 2021)
Summary: Integrating Spotnitz’s joining technique and Eigen’s distinction-union structure deepens clinical understanding of preverbal communication. This assimilated formulation helps to organize and work with defensive expressions configured around the early catastrophic experience of the infant. Taking the narcissistic transference as a starting point for the clinical work, Spotnitz’s and Eigen’s constructs are explored and combined in order to augment each approach and shed light on intervening. The join and the distinction-union structure both point to a therapeutic process that is beyond the binary of self-other, and are shown to mutually function by the nature of their structural association.
Keywords: Distinction-union structure; Eigen; Joining technique; Spotnitz